PENGARUH GAYA KEPEMIMPINAN TERHADAP MOTIVASI KERJA DAN KEPUASAN KERJA SERTA DAMPAK PADA KINERJA KARYAWAN (Studi Kasus BMT Bina Ihsanul Fikri Yogyakarta) - Andi Afrizal (Universitas Alma Ata, 2015)
Abstract The purpose of this study was to determine the effect of four kinds of leadership style path-goals are: directive leadership style, leadership style, supportive leadership style participatory and leadership style achievement orientation, on work motivation and job satisfaction and performance of employees at BMT Bina Ihsanul Fikri (BIF) in 2012. The data is taken from the total population of 62 people from sharing positions, the test data using multiple linear regression and path analysis in hypothesis testing. Results of the study, found that leadership style path goals positively affects employee performance mediated by motivation and job satisfaction of employees BMT BIF. The results could be used by future researchers. Keywords: Path-goals, motivation, satisfaction, employee performance